Flow Reversal of Fully Developed Mixed Convection in a Vertical Channel with Chemical Reaction. (9th May 2013) - Saleh, Habibis; Hashim, Ishak; Basriati, Sri
Abstract : The present analysis is concerned with the criteria for the onset of flow reversal of the fully developed mixed convection in a vertical channel under the effect of the chemical reaction. The governing equations and the critical values of the buoyancy force are solved and calculated numerically via MAPLE. Parameter zones for the occurrence of reversed flow are presented. The exothermic chemical reaction is found to enhance the flow reversal and made flow reversal possible for symmetrical walls temperature.